How Students' Perceptions in Narrative Class (The Lord of Flies) Through Online Collaboration Learning. - Noer Doddy Irmawati; Adhe Puspita Mayasari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Mariwan Hasan (2020), suggests that Golding’s novel can be used in a second language classroom to teach democratic values such as the right to free speech using reader-response theory. Curriculum requires that democratic values be taught through each subject, suggests that students can be taught about democratic values through classroom discussions and writing assignments based on the novel (Ghazal Kazim Syed, 2020). In addition to academic learning, researchers believe that students also gain confidence through the collaboration work. When students conform each other’s opinions in activities involving group work, it makes them confident and comfortable with each other. When the teacher is not around to ask a question, they will be less at pressure. against them (Cynthia S, 2020). The practice of collaborative learning in online education is increasing steadily as many curriculum creators and online course teachers are starting to understand its positive effects on the learning of students. This study aimed to analyze students' perceptions in narrative class (The Lord of Flies) through online collaboration learningu used a qualitative research design was followed by this study. As it is a study of perceptions, a qualitative methodology using a phenomenological approach, the participants of this study were twelve the eleventh grade students, data for this article was gathered through semi-structured interviews. The researcher checked part of the coding against each other to ensure trustworthiness of data. Keeping in light the usefulness of online collaboration learning shown in this study, it is recommended that teachers should take effort to include students in literature online discussion group. Furthermore, it is recommended that similar studies should be conducted in schools and colleges. As this study is recommended for future researchers to check the adaptability of the findings in other contexts.